Born to be free? Assessing the viability of releasing captive-bred wobbegongs to restock depleted populations - Lee, Kathryn A.; Huveneers, Charlie; Peddemors, Victor; Boomer, Andrew; Harcourt, Robert G. (Frontiers in Marine Science, 2015)
Large predatory fishes, such as sharks, play an important functional role within marine ecosystems. Restocking of depleted populations has been extensively studied for commercially or recreationally important teleost fish species; however, it has, to the best of our knowledge, never been successfully attempted and assessed on sharks. We evaluated whether fifteen captive-bred wobbegongs (Orectolobus maculatus) released into a small bay inhabited by wild sharks would survive and remain within a small ‘no-take’ marine reserve. The captive-bred sharks and twelve wild sharks were tagged with acoustic transmitters and their presence was monitored by an array of acoustic receivers. The detection rate of control tags was modelled against environmental variables to predict detection probabilities and account for days when environmental conditions hampered shark detections. The overall detection probability ranged from 28% to 38% and was most affected by wind direction. Wild wobbegongs showed clear seasonal patterns of attendance to the study site, with the highest probability of presence during the summer months. The captive-bred sharks did not display the same seasonal trend in occurrence. The age at which captive-bred sharks were released into the area affected residency periods. Four out of five adults remained in the area for up to three years post release, while all the juveniles permanently left the area within a year post-release. Three of the juveniles were detected on receivers up to 12 km from the study site. Therefore, if restocking of depleted populations of sharks is to be used as a conservation strategy, the age at which sharks are released must be considered.